2023
DOI: 10.1101/2023.03.21.533548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards a Foundation Model of the Mouse Visual Cortex

Abstract: Understanding the brain's perception algorithm is a highly intricate problem, as the inherent complexity of sensory inputs and the brain's nonlinear processing make characterizing sensory representations difficult. Recent studies have shown that functional models capable of predicting large-scale neuronal activity in response to arbitrary sensory input can be powerful tools for characterizing neuronal representations by enabling unlimited in silico experiments. However, accurately modeling responses to dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…To address this question, we made use of the fact that for many of the neurons in our dataset, we have measurements of how they respond to natural stimuli [6]. We leveraged a functional digital twin – a model that accurately predicted the response of a neuron to arbitrary visual stimuli [38] – to extract a functional bar code – a vector embedding f i that describes the input-output function of a neuron analogous to how our morphological bar codes describe their morphology (Fig. 7C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this question, we made use of the fact that for many of the neurons in our dataset, we have measurements of how they respond to natural stimuli [6]. We leveraged a functional digital twin – a model that accurately predicted the response of a neuron to arbitrary visual stimuli [38] – to extract a functional bar code – a vector embedding f i that describes the input-output function of a neuron analogous to how our morphological bar codes describe their morphology (Fig. 7C).…”
Section: Resultsmentioning
confidence: 99%
“…Functional digital twin can predict the functional response of the neurons to input stimuli such as natural movies. The input-output function of each neurons is described by a functional bar code f i [38]. Schematic adapted from Consortium et al [6] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we presented to the same neuronal population a static set of natural images as well as the identical set of natural movies used in the MICrONs data set. We then trained two different static image models: one directly on in vivo static responses, and another on in silico predicted responses to the identical static images from a recurrent neural network trained on movie stimuli (22). We found that the MEIs and DEIs generated from these two models were perceptually similar (Fig.…”
mentioning
confidence: 98%
“…Second, we wanted to determine if DEIs are robust across predictive models with distinct architecture trained on different stimulus domains. To do this, we developed a method to synthesize DEIs from the dynamic digital twin trained on natural movies in the MICrONS functional connectomics data set (9,22). Specifically, we presented to the same neuronal population a static set of natural images as well as the identical set of natural movies used in the MICrONs data set.…”
mentioning
confidence: 99%